Work-related and Non-work-related Lead Poisoning among Adults in Florida - Babajide Sadiq (University of North Florida, 2018)
The aim of this study was to identify whether adults with lead poisoning (blood lead level ≥10μg/dL) due to exposure to lead at their workplace have higher blood lead concentration levels compared to persons with lead poisoning who are not occupationally exposed. Data for this study were collected from the Florida Blood Lead Epidemiology Surveillance (ABLES) Program from 2008 to 2010 (n = 2246 adults). The demographic characteristics used for this study included age, gender, race, and ethnicity. The population shows that adults 47years of age have the highest number of cases of blood lead level ≥10μg/dL. In addition, male, white, and non-Hispanic individuals had the most individuals with blood lead level ≥10μg/dL. The modal number of cases was among persons working and residing in Hillsborough County - 34.4% county of exposure and 35.8% county of residence. The results show that those with lead poisoning due to occupational exposure have an average blood lead concentration level that is 2.5 μg/dL more than those who are not occupationally exposed.